ACTUAL PROBLEMS OF PREVENTIVE AND CORRECTION OF PRENOSOLOGICAL CHANGES IN THE MENTAL HEALTH STATUS OF PUPILS AND STUDENTS - Serheta , Ihor (Collection of scientific papers «ΛΌГOΣ», 2022)
Early diagnosis, adequate prevention and timely correction of pre-existing conditions are currently one of the most effective ways to preserve and strengthen the mental health of adolescents and young people, рupils and students. In this context, it should be noted that prenosological changes in the state of mental health as intermediate states between normality and pathology must be considered based on three leading positions: the first defines pre-clinical changes in the state of mental health or as certain health conditions that do not meet the criteria of the average statistical norm, or as certain subthreshold mental and behavioral disorders that can be isolated as an independent variant of pathological manifestations (individual manifestations of mental retardation, attention deficit hyperactivity disorder), the second – characterizes prenosological changes in the state of mental health as disturbances in the course of adaptation processes (various disturbances in the course of mental, psychophysiological and sociopsychological adaptation processes), the third – defines prenosological changes in the state of mental health as a state of pre-morbidity (early dysfunctional manifestations of psychopathology (neurotic reactions), neurological (speech disorders, cephalic syndrome) and somato-vegetative (astheno-vegetative manifestations) character